Porous polymer composite diaphragm and preparation method thereof

By using a porous polymer composite separator on the lithium-ion battery separator, the high heat resistance and porous structure of polyethersulfone is used to solve the problems of poor thermal stability of the separator at high temperature and insufficient electrolyte wetting, and higher battery performance is achieved.

CN119542676APending Publication Date: 2025-02-28JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807809.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor thermal stability at high temperatures, which can easily lead to short circuits in the battery and insufficient wetting properties of the electrolyte, affecting the electrochemical performance of the battery.

Method used

A porous polymer composite separator is used, and its coating is made of polyethersulfone as the main material. It forms a membrane structure with high porosity and high heat resistance by combining it with a polyolefin-based film.

Benefits of technology

It improves the thermal stability and electrolyte wetting properties of the diaphragm, enhances the lithium ion transmission ability, reduces the internal resistance of the diaphragm, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542676A_ABST
    Figure CN119542676A_ABST
Patent Text Reader

Abstract

The invention discloses a porous polymer composite diaphragm and a preparation method thereof, and relates to the technical field of batteries. The method comprises the following steps: 1, mixing polyether sulfone with a solvent, and fully dissolving to form a homogeneous solution, thereby obtaining feed liquid A; mixing and uniformly stirring an auxiliary agent and a solvent, adding an inorganic filler, and continuously stirring to uniformly disperse the inorganic filler to obtain a feed liquid B; 2, mixing the feed liquid A and the feed liquid B, and fully stirring to form slurry; 3, uniformly coating a base film with the slurry by adopting a gravure coating method to obtain a wet coating diaphragm; and 4, soaking the wet coating diaphragm into a coagulating bath, then soaking in water, washing, and drying to obtain the porous polymer composite diaphragm. The porous polymer composite diaphragm and the preparation method thereof provided by the invention have the beneficial effects that polyether sulfone is used as a main body material, so that the heat resistance, the dimensional stability and the electrolyte wettability of the diaphragm are improved, the internal resistance of a battery is reduced, and the safety and the electrochemical performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a porous polymer composite diaphragm and a preparation method thereof. Background Art

[0002] The diaphragm is one of the key materials in lithium-ion batteries. As an inert material, it mainly blocks electrons and allows ions to pass through. Its performance is closely related to the safety and electrochemical performance of the battery. The performance of the diaphragm determines the internal resistance and interface structure of the battery. A diaphragm with excellent performance has a profound impact on the overall performance of the battery.

[0003] The most widely used commercial diaphragm at present is the polyolefin microporous membrane, but it has some disadvantages. First, due to the low glass transition temperature and melting point of polyolefin, the prepared diaphragm has poor thermal stability, which is mainly manifested in that the diaphragm shrinks greatly or even melts when the temperature rises, which can easily lead to battery short circuit and affect battery safety; second, polyolefin is generally a non-polar polymer, and the electrolyte wettability of the prepared diaphragm is poor, which has a certain impact on the electrochemical performance of the battery. With the continuous development of new energy vehicles and 3C consumer batteries, the product side has higher requirements for battery performance. In order to make up for the shortcomings of polyolefin diaphragms, the diaphragm industry has seen the emergence of products with coated polyolefin diaphragms as the mainstream. The coating layer is based on improving the thermal stability of the diaphragm and improving the battery rate performance. The ceramic coating with better heat resistance or the polymer coating such as polyvinylidene fluoride and polymethyl methacrylate with better electrode adhesion are applied to the polyolefin diaphragm, which has a certain improvement effect.

[0004] The presence of ceramic coating reduces the thermal shrinkage of the diaphragm on the one hand; however, due to the high density of ceramic particles, it undoubtedly has a negative impact on the surface density of the diaphragm and the internal resistance of the battery. At the same time, the ceramic material itself has a high hardness, and the coating formed relies on the adhesive to adhere to the surface of the polyolefin diaphragm, which does not prevent the diaphragm from breaking and melting, that is, it does not improve the diaphragm rupture temperature.

[0005] Therefore, in order to solve the above problems, the present invention provides a porous polymer composite diaphragm and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide a porous polymer composite diaphragm and a preparation method thereof to solve the problems raised in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a porous polymer composite diaphragm comprises the following steps: Step 1: Mix polyethersulfone with a solvent and fully dissolve them to form a homogeneous solution to obtain liquid A; mix the auxiliary agent with the solvent, stir them evenly, add an inorganic filler, continue stirring to make them evenly dispersed, and obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: uniformly coating the slurry on the base film by gravure coating to obtain a wet coating separator; Step 4: Immerse the wet coating membrane in a coagulation bath, then wash with water, and dry to obtain a porous polymer composite membrane, wherein the coating thickness is 2-6 μm and the porosity is 25-75%.

[0008] More optimally, the weight average molecular weight of the polyethersulfone is 35000 g / mol-85000 g / mol.

[0009] More optimally, the slurry comprises the following components: by weight, 8-15 parts of polyethersulfone, 100 parts of solvent, 0.5-5 parts of auxiliary agent, and 0.5-7 parts of inorganic filler.

[0010] More optimally, the solvent includes one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0011] More optimally, the auxiliary agent includes one or more of polyvinyl pyrrolidone, a silane coupling agent, and a fatty acid.

[0012] More optimally, the inorganic filler includes one or more of aluminum oxide, titanium oxide, magnesium oxide, silicon oxide, and boehmite, and the average particle size thereof is 20-750 nm.

[0013] More optimally: the temperature of the coagulation bath is 20-50° C., and its main components include N-methylpyrrolidone and water, wherein the mass fraction of N-methylpyrrolidone in the coagulation bath is 25-65wt%; More optimally: the specific process of drying is to dry the moisture in an oven at 50°C, 55°C, and 60°C respectively.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a porous composite diaphragm with a heat-resistant polymer as the main coating and a preparation method thereof. Polyethersulfone is used as the main material to attach a polymer coating on the surface of a polyolefin base film to prepare a composite membrane. The high strength, high heat resistance and good electrolyte wettability of polyethersulfone are used to improve the dimensional stability of the diaphragm and promote lithium ion transmission. At the same time, compared with other heat-resistant polymers such as polyimide, aramid and other polymer coating materials, polyethersulfone has the advantages of simple formula, convenient operation and low cost. The details are as follows: (1) The glass transition temperature of polyethersulfone is between 220℃ and 235℃, and the heat deformation temperature is about 205℃. It has excellent creep resistance and dimensional stability at high temperatures. Based on the good heat resistance of polyethersulfone itself, the porous polymer composite membrane has an improvement in the thermal shrinkage rate of the membrane compared to the polyolefin-based membrane. At the same time, polyethersulfone has a low density and a low bulk density after film formation. Compared with ceramic-coated membranes that achieve the same heat resistance, it can increase the energy density of the battery. (2) Compared with traditional ceramic membranes, the coating formed by the porous polymer composite membrane has a porous polyethersulfone membrane as the main structure. This main structure is tightly combined with the base membrane through a mechanical interlocking structure. When the temperature reaches the melting point of the base membrane but does not reach the glass transition temperature of polyethersulfone, the polymer in the coating undergoes a secondary transformation and no chain segment movement occurs. The membrane can rely on the high temperature stability and certain toughness of the coating to maintain membrane integrity and increase its membrane rupture temperature; (3) The porous polymer composite membrane has electrolyte-philic functional groups, and its chain segments are amorphous and the porous structure they form can enhance the electrolyte wettability of the membrane. Its liquid absorption rate, electrolyte contact angle and ion conductivity have obvious advantages over polyolefin-based membranes and traditional ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The figure is a flow chart of the preparation of porous polymer composite membrane; Figure 2 This is the internal microscopic morphology of the polyethersulfone coated diaphragm; Figure 3 It is the structural formula included in polyethersulfone. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] It should be noted that the purchasers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: in the following embodiments, the auxiliary agent is polyvinyl pyrrolidone, model K30; the inorganic filler is a compound of 20nm and 200nm alumina, each 50wt%; and the solvent is N-methyl-2-pyrrolidone.

[0018] Embodiment 1: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 10 parts of polyethersulfone (weight average molecular weight 75000 g / mol) were mixed with 80 parts of solvent, and fully dissolved to form a homogeneous solution to obtain liquid A; 0.5 parts of auxiliary agent were mixed with 20 parts of solvent, and after stirring evenly, 0.5 parts of inorganic filler were added, and stirring was continued to make it evenly dispersed to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0019] Embodiment 2: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 10 parts of polyethersulfone (weight average molecular weight 75000 g / mol) are mixed with 80 parts of solvent, and fully dissolved to form a homogeneous solution to obtain liquid A; 1 part of auxiliary agent is mixed with 20 parts of solvent, and after stirring evenly, 2 parts of inorganic filler are added, and stirring is continued to make it evenly dispersed to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0020] Embodiment 3: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 10 parts of polyethersulfone (weight average molecular weight 75000 g / mol) were mixed with 80 parts of solvent, and fully dissolved to form a homogeneous solution to obtain liquid A; 1 part of auxiliary agent was mixed with 20 parts of solvent, and after stirring evenly, 3 parts of inorganic filler were added, and stirring was continued to make it evenly dispersed to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0021] Embodiment 4: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 12 parts of polyethersulfone (weight average molecular weight 75000 g / mol) were mixed with 80 parts of solvent, and fully dissolved to form a homogeneous solution to obtain liquid A; 1 part of auxiliary agent was mixed with 20 parts of solvent, and after stirring evenly, 3 parts of inorganic filler were added, and stirring was continued to make it evenly dispersed to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0022] Example 5: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 12 parts of polyethersulfone (weight average molecular weight of 75000 g / mol) and 80 parts of solvent (N-methyl-2-pyrrolidone) are mixed and fully dissolved to form a homogeneous solution to obtain liquid A; 2 parts of auxiliary agent and 20 parts of solvent (N-methyl-2-pyrrolidone) are mixed and stirred evenly, and then 3 parts of inorganic filler are added and stirred continuously to make it dispersed evenly to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0023] Example 6: A method for preparing a porous polymer composite membrane, comprising the following steps: Step 1: 13 parts of polyethersulfone (weight average molecular weight 75000 g / mol) were mixed with 80 parts of solvent, and fully dissolved to form a homogeneous solution to obtain liquid A; 2 parts of auxiliary agent were mixed with 20 parts of solvent, and after stirring evenly, 3 parts of inorganic filler were added, and stirring was continued to make it evenly dispersed to obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: The slurry is uniformly coated on a 9 μm polyethylene film (porosity 45-50%) by gravure coating to obtain a wet coating separator; Step 4: Soak the wet coated membrane in a coagulation bath at 45°C, wherein the coagulation bath is a mixture of N-methylpyrrolidone (NMP) and water, and the mass fraction of NMP is 60%. Then, wash it with water, and dry the water in an oven at 50°C, 55°C, and 60°C, respectively, to obtain a porous polymer composite membrane with a coating thickness of 5 μm.

[0024] Comparative Example 1: The diaphragm is a polyethylene film with a high porosity of 9µm and is not plated.

[0025] Comparative Example 2: Compared with Example 4, a different polyethersulfone was used as the main coating material (weight average molecular weight was 30000 g / mol); Comparative Example 3: Compared with Example 4, the coating thickness is 1 μm.

[0026] Detection experiment: (1) Thermal shrinkage test The diaphragms obtained in the examples and comparative examples were cut into 20×10 cm 2 The square was placed between two A4 papers and placed in a constant temperature drying oven. The constant temperature was set to 130°C and the constant temperature treatment was performed for 1 hour. The size change ratio of the diaphragm before and after the heat treatment was compared and calculated.

[0027] (2) Ionic conductivity test The diaphragms obtained in the examples and comparative examples were assembled into a stainless steel / diaphragm / stainless steel symmetrical battery, and 15uL of electrolyte (1M LiPF6 in ethylene carbonate / dimethyl carbonate / diethyl carbonate) was used to test the bulk impedance R, which was calculated according to the ionic conductivity formula = D / (R×S), where R is the electrode contact area and L is the diaphragm thickness.

[0028] (3) Electrolyte contact angle test The diaphragms obtained in the examples and comparative examples were cut into strips with a width of 1 cm and a length of 20 cm. The two ends were straightened and fixed on the sample stage. The drop volume was set to 2 µL. The angle at which the droplet contacted the strip was the electrolyte contact angle.

[0029] (4) Liquid absorption test The separators obtained in the examples and comparative examples were cut into pieces of 5×5 cm. 2 The mass of a square is defined as m0. It is immersed in electrolyte for 30 minutes. After removal, the electrolyte on its surface is wiped off and the mass at this time is defined as m1. The liquid absorption rate is calculated as (m1 / m0-m1).

[0030] (5) Film rupture temperature test The diaphragms obtained in the examples and comparative examples were cut into 20×10 cm 2 The square was placed between two A4 papers and placed in a constant temperature drying oven. The starting constant temperature was set to 130°C. Each constant temperature treatment lasted 10 minutes with a temperature interval of 5°C until the diaphragm ruptured.

[0031] (6) Tensile strength test The diaphragms obtained in the examples and comparative examples were cut into strips with a width of 1.5 cm and fixed in a fixture of a universal tensile machine with a fixed spacing, and biaxially stretched at a rate of 25 cm / min. The strength of the strips when they broke was the tensile strength.

[0032] The obtained data are shown in the following table: Table 1

[0033] Conclusion: The thermal shrinkage rate of the porous composite diaphragm in the above embodiment is <6%, the tensile strength is 180Mpa-230MPa, and the membrane breaking temperature is >180℃, which is greatly improved compared with Comparative Example 1. It can be seen that the formation of a polyethersulfone coating on the base film is beneficial to improving the heat resistance, dimensional stability and toughness of the diaphragm under high temperature conditions. At the same time, the liquid absorption rate of the porous composite diaphragm in the above embodiment is 150%-270%, and the ion conductivity is 2.2mS / cm-2.8mS / cm. The polyethersulfone coated diaphragm has good electrolyte wettability, which is beneficial to improving the lithium ion transport capacity and reducing the internal resistance of the diaphragm, which is in line with practical applications. By comparing Example 2 with Example 3, it can be seen that when the content of inorganic particles increases, the liquid absorption rate increases while the ionic conductivity decreases slightly. This is because the inorganic particles increase their free volume in the polymer coating, but cause the surface density and internal resistance to increase; by comparing Example 4 with Example 5, it can be seen that when the content of the auxiliary agent is large, the film-forming property is better due to the reduction in pore size and porosity, resulting in a decrease in its liquid absorption rate and an increase in tensile strength; among the above embodiments, Example 4 has a better overall performance, wherein, compared with Example 4, the molecular weight of the polyethersulfone used to prepare the diaphragm in Comparative Example 2 is reduced, and when the coating of the same thickness is reached, the thermal stability of the diaphragm is reduced; compared with Example 4, the thickness of the prepared polyethersulfone coating in Comparative Example 3 is reduced, and its thermal stability is also reduced.

[0034] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous polymer composite membrane, characterized in that: The following steps are involved: Step 1: Mix polyethersulfone with a solvent and fully dissolve them to form a homogeneous solution to obtain liquid A; mix the auxiliary agent with the solvent, stir them evenly, add an inorganic filler, continue stirring to make them evenly dispersed, and obtain liquid B; Step 2: Mix liquid A and liquid B, and stir thoroughly to form a slurry; Step 3: uniformly coating the slurry on the base film by gravure coating to obtain a wet coating separator; Step 4: Immerse the wet coating membrane in a coagulation bath, then wash with water, and dry to obtain a porous polymer composite membrane, wherein the coating thickness is 2-6 μm and the porosity is 25-75%.

2. The method for preparing a porous polymer composite membrane according to claim 1, characterized in that: The weight average molecular weight of the polyethersulfone is 35000 g / mol-85000 g / mol.

3. The method for preparing a porous polymer composite membrane according to claim 1, characterized in that: The slurry comprises the following components: by weight, 8-15 parts of polyethersulfone, 100 parts of solvent, 0.5-5 parts of auxiliary agent, and 0.5-7 parts of inorganic filler.

4. The method for preparing a porous polymer composite membrane according to claim 3, characterized in that: The solvent includes one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

5. The method for preparing a porous polymer composite membrane according to claim 3, characterized in that: The auxiliary agent includes one or more of polyvinyl pyrrolidone, a silane coupling agent, and a fatty acid.

6. The method for preparing a porous polymer composite membrane according to claim 3, characterized in that: The inorganic filler includes one or more of aluminum oxide, titanium oxide, magnesium oxide, silicon oxide, and boehmite, and the average particle size thereof is 20-750 nm.

7. The method for preparing a porous polymer composite membrane according to claim 1, characterized in that: The main components of the coagulation bath include N-methylpyrrolidone and water, wherein the mass fraction of N-methylpyrrolidone in the coagulation bath is 25-65wt%.

8. The method for preparing a porous polymer composite membrane according to claim 7, characterized in that: The temperature of the coagulation bath is 20-50°C.

9. The method for preparing a porous polymer composite membrane according to claim 1, characterized in that: The specific process of the drying is to dry the moisture in an oven at 50°C, 55°C and 60°C respectively.

Citation Information

Cited By

  • High-heat-resistance battery diaphragm and preparation method thereof

    CN120749348A